Study on Doppler Findings and Neonatal Outcome in Fetal Growth Restriction: A Teaching Hospital Based Study - Kiran Kumar Neelapu (Asian Journal of Medical Radiological Research, 2019)
Background: Intrauterine growth restriction (IUGR) is defined as sonographic estimated fetal weight <10th percentile for gestational age.  Intrauterine growth retardation (IUGR) is associated with an increased risk of perinatal mortality, morbidity, and impaired neurodevelopment. Subjects and Methods: A total of 65 women with singleton pregnancies of 28 weeks and above, who were diagnosed with fetal growth restriction and were evaluated by Doppler studies according to inclusion and exclusion criteria. Results: On analysing the antenatal Doppler studies, abnormal CP ratio, elevated umbilical artery PI and reduced MCA PI were found in 12, 16 and 32 fetuses respectively. CP ratio showed a sensitivity of 19.61 % and specificity of 85.71 % with a positive predictive value of 83.33 % and negative predictive value of 22.64 %. Pulsatility index of umbilical artery showed sensitivity of 23.53 % and specificity of 71.43 %, with Positive predictive value of 75.00 % and Negative predictive value of 20.41 %. Pulsatility index of MCA showed a sensitivity of 52.94 % and specificity of 64.29 % with PPV of 84.38 % and NPV of 27.27 %. Conclusion: The IUGR is an important cause of perinatal morbidity and mortality. Antenatal Doppler analysis of UA and MCA can predict neonatal outcome in FGR foetuses. The fetal growth restriction has considerable perinatal and long term effects on the neonate. Once it is suspected careful Doppler evaluation can identify fetuses at risk for poor neonatal outcome.